2018
DOI: 10.1007/s12035-018-1291-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Changes the Site of RAGE Expression from Endothelial Cells to Neurons in Different Brain Areas

Abstract: The receptor for advanced glycation endproducts (RAGE) is a transmembrane, immunoglobulin-like receptor that interacts with a broad repertoire of extracellular ligands. RAGE belongs to a family of cell adhesion molecules and is considered a key receptor in the inflammation axis and a potential contributor to the neurodegeneration. The present study aimed to investigate the content and cell localization of RAGE in the brain of Wistar rats subjected to systemic inflammation induced by a single dose of lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…RAGE immunoreactivity revealed that RAGE abundance increased in the male experimental cohorts only, not in the female cohorts. The increase, approximately 2.5 fold, was statistically significant and consistent with literature values [ [33] , [34] , [35] ]. The magnitude of change in RAGE abundance did not change between 1 day and 14 days unlike TNFα and IL-1β, which had both decreased by the 14 day mark ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…RAGE immunoreactivity revealed that RAGE abundance increased in the male experimental cohorts only, not in the female cohorts. The increase, approximately 2.5 fold, was statistically significant and consistent with literature values [ [33] , [34] , [35] ]. The magnitude of change in RAGE abundance did not change between 1 day and 14 days unlike TNFα and IL-1β, which had both decreased by the 14 day mark ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…As our effort to develop RAGE radiotracers continues, we also hope to have an animal model with upregulated RAGE that we can use to evaluate newly developed radiotracers in vivo. LPS, a known toll-like receptor 4 (TLR4) ligand, has long been used to induce peripheral inflammation and, in the classic LPS model of inflammation, RAGE has been shown to be increased modestly (1.5 – 3-fold) in male rodents [ [33] , [34] , [35] ]. In the final part of this paper we describe our investigation of such LPS-treated mice as an animal model with increased RAGE expression and its potential for use in evaluating new RAGE imaging agents in the future.…”
Section: Resultsmentioning
confidence: 99%
“…However, the amounts of plasma AGEs, which can stimulate the aggregation of specifically modified proteins, are different in Alzheimer's and Parkinson's disease patients in a sexdependent manner, thus requiring a careful interpretation of test results 104 . Similar to AGEs, RAGEs are significantly or markedly expressed in many areas of the brain, such as the cortex, hippocampus, cerebellum, and substantia nigra [105][106][107] during the development of neurodegenerative diseases. Activated microglial cells produce and secrete AGE-albumin to induce RAGE expression in neurons and promote neuronal cell death, thereby contributing to neurodegenerative disorders 4,108 .…”
Section: Ages and Neurodegenerative Diseasesmentioning
confidence: 99%
“…There is also strong evidence for endosomal TLR3 expression in neurons, where the receptor not only contributes to mediating cellular responses to pathogens, but also plays a role in regulation of neuronal morphology (Hung et al, 2018). Neuronal expression of RAGE is also well documented (Sasaki et al, 2001), with this receptor heavily implicated in the pathogenesis of neurodegenerative disorders, particularly Alzheimer's disease (Cai et al, 2016), and in contributing to neurological sequelae associated with diabetes (Toth et al, 2007) and other systemic pathologies with an inflammatory element (Gasparotto et al, 2019). Receptors for TGF-β are also expressed in neurons, where they have been implicated in mediating cell fate in response to insult (König et al, 2005).…”
Section: P38 Mapk -Mk2 Signaling Axis At Confluence Of Inflammatory and Synaptic Signalingmentioning
confidence: 99%